if Sn the sum of first n terms of an a.p is given by Sn=5n^2+3n then find its nth term ?? (please explain you procedure)

Asked by ANVESH agarwal | 25th Oct, 2010, 07:46: PM

Expert Answer:

Dear Student,
 
According to the question, the sum of first n term of the AP is given by,
 
Sn = 5n2 + 3n
 
Now, the sum of first (n-1) terms will be given by
 
Sn-1 = 5(n-1)2 + 3(n-1)
 
=> Sn-1 = 5n2 + 5 - 10n + 3n - 3 = 5n2 - 7n + 2
 
Now, the difference between Sn and Sn-1 is equal to the nth term,
 
Sn - Sn-1 = 5n2 + 3n - 5n2 + 7n - 2
 
=> Tn = 10n - 2
 
 
Regards Topperlearning.

Answered by  | 25th Oct, 2010, 10:51: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.